Evolusi Pendidikan dalam Islam : Periode Mekkah dan Madinah - Selin Radiana (UPT Publikasi Ilmiah, 2026)
This study explores the evolution of Islamic education during the Mecca and Medina periods with the aim of uncovering the transformation of informal education into a structured and inclusive system. The problem with this research is the lack of comprehensive studies on how Islamic education has adapted to social, political, and cultural changes in both periods, as well as their implications for Islamic education today. The purpose of this study is to analyze comparative educational methods, the roles of figures, and the driving factors of evolution, such as the Hijrah, to understand their historical contributions in shaping the principles of Islamic education. The method used in this study is a literature study. All data and information were obtained from various sources and related literature, including scientific journals, research articles, and the writings of experts discussing the historical thinking of the development of Islamic education during the Mecca and Medina periods. The results show that Islamic education during the Mecca period focused on instilling moral values and monotheism amidst all forms of rejection from the Quraysh. Meanwhile, in Medina, education became more holistic with Holaqoh in the mosque, and the integration of practical sciences. This evolution opened up access to Islamic education to form the foundation of a more complete civilization. Based on the results of this research, we hope to be able to integrate these evolutionary values into contemporary Islamic education. This research will be very useful in increasing insight and understanding, enabling innovation in contemporary Islamic education to become more moral.